Manajemen Isu Bakso A Fung: Studi Kasus Insiden Kerupuk Kulit Babi - Annisa Alfannafiisah; Chaer Ranie Cahyaningsih; Nabilah Akhsaniyah; Linka Azzahra (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study was conducted to determine how issue management was carried out by Bakso A Fung after the pork skin cracker incident. This study uses a qualitative research method with literature study techniques. From this incident, of course, Bakso A Fung requires several management strategies in managing this problem. This issue management strategy aims for the company to be able to know, observe, carry out, and resolve existing problems. The Bakso A Fung company identified the problem because this incident caused many concerns among consumers, especially consumers who are very concerned about the halal aspect of food products. The Bakso A Fung company responded quickly to the problem that occurred at one of its outlets in Bali.